Automatic Implantable Cardioverter Defibrillator in Electroconvulsive Therapy. Issue 1 (March 2015) - Bryson, Ethan O.; Popeo, Dennis M.; Briggs, Mimi C.; Pasculli, Rosa M.; Kellner, Charles H.
Abstract : Abstract: As the number of patients with implantable cardiac devices increases so too does the frequency with which these individuals present for electroconvulsive therapy (ECT). The rationale for deactivating an automatic implantable cardioverter defibrillator before ECT has been made based on the concern that artifacts generated during treatment could be interpreted as a treatable rhythm by the internal device, resulting in a discharge. We believe that the risk of inappropriate discharge during ECT is very low and outweighed by the considerable benefit of an active device being able to more quickly treat a malignant dysrhythmia.